Extracellular Protease Activity of Enteropathogenic Escherechia coli on Mucin Substrate - SRI BUDIARTI; NISA RACHMANIA MUBARIK (HAYATI Journal of Biosciences, 2007)
Enteropathogenic Escherichia coli (EPEC) causes gastrointestinal infections in human. EPEC invasion was initiated by attachment and aggressive colonization on intestinal surface. Attachment of EPEC alter the intestine mucosal cells. Despite this, the pathogenic mechanism of EPEC infectior has not been fully understood. This research hypothesizes that extracellular proteolytic enzymes is necessary for EPEC colonization. The enzyme is secreted into gastrointestinal milieu and presumably destroy mucus layer cover the gastrointestinal tract. The objective of this study was to assay EPEC extracellular protease enzyme by using mucin substrate. The activity of EPEC extracellular proteolytic enzyme on 1% mucin substrate was investigated. Non-pathogenic E. coli was used as a negative control. Positive and tentative controls were Yersinia enterocolitica and Salmonella. Ten EPEC strains were assayed, seven of them were able to degrade mucin, and the highest activity was produced by K1.1 strain. Both positive and tentative controls also showed the ability to digest 0.20% mucin. Key words: EPEC, protease, mucin, diarrhea